2013
DOI: 10.3109/0886022x.2013.846865
|View full text |Cite
|
Sign up to set email alerts
|

To study the effect of monosodium glutamate on histomorphometry of cortex of kidney in adult albino rats

Abstract: Thousands of chemicals are being used recently in our new high tech foods like ready to eat Japanese, Chinese, packaged and tinned foods. Most food additives act as either preservatives or flavor enhancers like monosodium glutamate (MSG), a sodium salt of glutamic acid. The present study investigated the effect of intraperitoneally administered MSG on cortex of the kidneys of adult albino Wistar rats and compared with control group. The histomorphometry done by calibrating with ocular micrometer on kidney tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 9 publications
5
23
0
1
Order By: Relevance
“…Other mechanisms for the tubular lesions might involve reactive intermediates or oxidative stress, or both Alden and Frith, (1992) and Ebaid and Tag, (2012). These results agreed with Eweka (2007), Abass and Abd El-Haleem (2011), Eraque (2011), Afeefy et al (2012, Onaolapo et al (2013) and Dixit, et al (2014) who postulated that the degenerative effect of MSG on the cortex and medulla of kidney was due to the direct effect of toxins on cells of kidney which coincided with (Porter, 1994) who reported that one of the possible mechanism for the tubular lesions was the direct toxic effect on the cell function.…”
Section: Discussionsupporting
confidence: 85%
“…Other mechanisms for the tubular lesions might involve reactive intermediates or oxidative stress, or both Alden and Frith, (1992) and Ebaid and Tag, (2012). These results agreed with Eweka (2007), Abass and Abd El-Haleem (2011), Eraque (2011), Afeefy et al (2012, Onaolapo et al (2013) and Dixit, et al (2014) who postulated that the degenerative effect of MSG on the cortex and medulla of kidney was due to the direct effect of toxins on cells of kidney which coincided with (Porter, 1994) who reported that one of the possible mechanism for the tubular lesions was the direct toxic effect on the cell function.…”
Section: Discussionsupporting
confidence: 85%
“…Some of the sections of kidney tissue at E3 group showed dilatation of renal tubules with intralumenal hyaline casts, swelling in Bowman's capsule, injured brush border of proximal convoluted tubules, necrotic lesions of the urinary tubules. Similar findings were observed in rat kidney studies done by Abass and Abd El-Haleem (2011) and Dixit et al (2014). MSG generates reactive oxygen species (ROS) causing oxidative stress by endogenous antioxidants depletion in the kidneys, which leads to lipids, proteins, DNA, RNA oxidation, which in the end will produce cellular alterations (Paul et al, 2012, Sharma et al, 2014.…”
Section: Discussionsupporting
confidence: 71%
“…Third group (MSG group): Rats were injected intraperitoneally with MSG (Sigma-Aldrich Co, St. Louis, MO, USA.) Sigma-Aldrich,) dissolved in physiological saline 4 g/kg of body weight for 7 successive days, then left without treatment until the 30th day of the experiment [33].…”
Section: Experimental Designmentioning
confidence: 99%